The drama of reality television : lives of youth in liquid modern times - Ligocki, Danielle T. (Brill Sense, 2018)
In The Drama of Reality Television: Lives of Youth in Liquid Modern Times , the author offers a glimpse into the lives, viewing habits, and opinions of today's Generation Z. While reality television is quite often viewed as just a guilty pleasure, the conversations that the author had with young people show that reality television is a major pedagogical force in the lives of young viewers. This is compounded by our current liquid modern time period; a time in which everything is fluid, there are no solid bonds and people are disposable. The author shares the incredible conversations that she had with seven honest, insightful pre-teenagers to give us a deeper understanding of the ways in which just a 'guilty pleasure' is working to deeply impact the lives of young people.
Keywords: Reality television programs -- Social aspects -- United States.; Television and youth -- United States.; Youth -- United States -- Attitudes.; Télévision et jeunesse -- États-Unis.; Jeunesse -- États-Unis -- Attitudes.; PERFORMING ARTS / Reference; Reality television programs -- Social aspects; Television and youth; Youth -- Attitudes; United States